Characterization of the Portuguese pediatric population with Cystic Fibrosis and their parents: cross-sectional study - Guimarães, Catarina (2021)
Background: Cystic fibrosis is a chronic disease with multiple associated challenges, not only for the children/adolescents but also for their parents/caregivers. To the best of the authors knowledge, to this date there are no published studies characterizing the portuguese pediatric population with cystic fibrosis. Aims: To characterize children/adolescents with Cystic Fibrosis in terms of: physiotherapy, hospitalizations in 2018, as well as medication taken in the previous two weeks. We also aimed to characterize the parents/caregivers in terms of sociodemographic data, caregivers’ role (sleep habits, service and work activities) and equipment sterilization habits for medication administration.  Methods: Cross-sectional study with a total sample of 28 parents/caregivers and 28 children/adolescents (n=28) - 14 were female with an average age of 12,14 ± 3,99 years old. The online question forms – Sample Selection and Characterization Questionnaire and CarerQol - were sent to the parents/caregivers, through the Portuguese Association of Cystic Fibrosis database. Results: 69.23% (n=18) children/adolescents had physiotherapy once or twice a week. Most parents/caregivers sterilized the equipment used for medication admission (53.57%) but 33.33% considered that soap and water washing was an effective sterilization. Conclusion: We found that children/adolescents with Cystic Fibrosis do not undergo physiotherapy at the recommended frequency. Also, most parents/caregivers have appropriate sterilization habits, although some of them do not have the correct information on how to perform effective sterilization.   Keywords: Cystic Fibrosis; Smoke Habits; Physiotherapy; Sterilization; Pediatric Population